Repetition effects in human ERPs to faces. (July 2016) - Schweinberger, Stefan R.; Neumann, Markus F.
Abstract: In the present paper, we review research conducted over the past 25 years addressing the effects of repeating various kinds of information in faces (e.g., pictorial, spatial configural, identity, semantic) on different components in human event-related brain potentials (ERPs). This body of evidence suggests that several ERP components are systematically linked to different functional components of face identity processing. Specifically, we argue (1) that repetition of the category of faces (categorical adaptation) strongly affects the occipitotemporal N170 amplitude, which is systematically suppressed when a face is preceded by another face, irrespective of its identity, whereas (2) the prototypicality of a face's second order spatial configuration has a prominent effect on the subsequent occipitotemporal P200. Longer-latency repetition effects are related to the processing of individual facial identities. These include (3) an ERP correlate of the transient activation of individual representations of repeated faces in the form of an enhanced occipitotemporal N250r as seen in repetition priming experiments, and (4) a correlate of the acquisition of individual face identity representations during learning as seen in a topographically similar long-lasting N250 effect. Finally, (5) the repetition of semantic information in familiar person recognition elicits a central-parietal N400 ERP effect. We hope that this overview will encourage researchers to further exploit the potential of ERPs to provide a continuous time window to neuronal correlates of multiple processes in face perception under comparatively natural viewing conditions.